1985
DOI: 10.1073/pnas.82.19.6455
|View full text |Cite
|
Sign up to set email alerts
|

Conserved features of eukaryotic hsp70 genes revealed by comparison with the nucleotide sequence of human hsp70.

Abstract: We have determined the nucleotide sequence of the human hsp7O gene and 5' flanking region. The hsp7O gene is transcribed as an uninterrupted primary transcript of 2440 nucleotides composed of a 5' noncoding leader sequence of 212 nucleotides, a 3' noncoding region of 242 nucleotides, and a continuous open reading frame of 1986 nucleotides that encodes a protein with predicted molecular mass of 69,800 daltons. Upstream of the 5' terminus are the canonical TATAAA box, the sequence ATTGG that corresponds in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
386
1
9

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(404 citation statements)
references
References 38 publications
8
386
1
9
Order By: Relevance
“…The human hsp70 53 was cloned into pcDNA3.1(+)-TRP2-ns vector at the unique sites of BamHI and NotI (TRP2hsp70) using standard PCR clone strategy and primers: 5 0 CGGGATC CATGGCCAAAGCCGCGGCAGTC and 5 0 ATAAGAAT GCGGCCGCCTAATCTACCTCCTCAATGGT (P2). TRP2 was generated by cloning truncated mouse TRP2 including stop codon into pcDNA 3.1(+) vector at the unique sites of NheI and BamHI using primers: P1 and 5 0 CGGG ATCCCTATGAGAGAGTTGTGGACCAAACTGG.…”
Section: Dna Constructsmentioning
confidence: 99%
“…The human hsp70 53 was cloned into pcDNA3.1(+)-TRP2-ns vector at the unique sites of BamHI and NotI (TRP2hsp70) using standard PCR clone strategy and primers: 5 0 CGGGATC CATGGCCAAAGCCGCGGCAGTC and 5 0 ATAAGAAT GCGGCCGCCTAATCTACCTCCTCAATGGT (P2). TRP2 was generated by cloning truncated mouse TRP2 including stop codon into pcDNA 3.1(+) vector at the unique sites of NheI and BamHI using primers: P1 and 5 0 CGGG ATCCCTATGAGAGAGTTGTGGACCAAACTGG.…”
Section: Dna Constructsmentioning
confidence: 99%
“…The MIC gene transcriptional regulatory sequences contain heat-shock elements similar to those in the human Hsp70 promoter. Since genotoxic chemotherapeutic agents such as alkylating, cytotoxic, antimitotic and antimetabolic substances, activate the Hsp70 promoter (Hunt and Morimoto, 1985;Groh et al, 1996) via binding of HSF-1, thereby inducing gene transcription, similar mechanisms, may explain the induction of MIC-A/B expression by fotemustine (Liu et al, 1996). Though induction of MIC-A/B by chemotherapy and subsequent presence of an NKG2D þ inflammatory infiltrate was only investigated in one patient, our previous studies in cutaneous melanoma demonstrated changes in the inflammatory infiltrates at different tumour stages, which were associated with changes in MIC-A/B expression (Vetter et al, 2002), thus strengthening the relevance of these findings in this one patient.…”
Section: Loss Of Nonclassical Mhc Molecules Mic-a/b Expression Cs Vetmentioning
confidence: 99%
“…HSP-70 mRNA was detected using a 30-mer oligonucle otide probe with the sequence 3'-GG TAC CAC GAC TGG TTC TAC TTC CTC TAG C-5' (Nowak et aI., 1990b). This sequence, which is reported to be specific for the inducible form of HSP-70 mRNA (Miller et aI., 1987(Miller et aI., ,1991, corresponds to a highly conserved region of the HSP-70 coding sequence, amino acids 122-129 of hu man HSP-70 (Hunt and Morimoto, 1985). As a control for the HSP-70 probe, a 30-mer oligonucleotide with the com plementary sequence was also tested.…”
Section: In Situ Hybridizationmentioning
confidence: 99%